Cat & cat. 3, My dad has a date... ew! - Cazenove, 1969-; 1967- (Papercutz, 2020)
"Since her dad started going out with Samantha, young Cat and her feisty cat, Sushi, have had plenty of time to entertain themselves. But with Samantha comes her video game-addicted son, Virgil. Now, Virgil, Cat, and her cat must choose between banding together to fight against boredom or compete for the run of the house. Just when things are finally going smoothly, the clan takes a Euro trip that the continent might not be fully prepared for!"--Amazon.